Técnicas de extracción en el donante a corazón parado. - Crespi Martínez, F.; Fuentes Márquez, I.; Resel, Luis; Gómez Vegas, Ángel; Silmi Moyano, A.; Blázquez Izquierdo, J. (Clínicas Urológicas de la Complutense, 1999)
Sin resumen